Population dynamics and orientation of the central Andean cushion Azorella compacta - Kleier, Catherine; Trenary, Tim; Graham, Eric A; Rundel, Philip W (PeerJ PrePrints, 2014)
Azorella compacta (llareta; Apiaceae), a large woody cushion plant, is a remarkable species forming dense cushions and characterizing the high elevation rocky slopes of the central Andean Altiplano. Field studies of an elevational gradient of A. compacta within Lauca National Park in northern Chile found a reverse J-shape distribution of size classes of individuals with abundant small plants at all elevations. A new elevational limit for A. compacta was found at 5250 m. A series of cushions marked 14 years earlier showed either slight shrinkage or small degrees of growth up to 2.2 cm yr-1. Despite their irregularity in growth, cushions of A. compacta show a strong orientation, centered on a north-facing aspect and angle of about 20o from horizontal. This exposure to maximize solar irradiance closely matches previous observations of a population favoring north-facing slopes at a similar angle. Populations of A. compacta appear to be stable, or even expanding, with young plants abundant and recolonization of disturbed habitats.
Keywords: Andes; Parque Nacional Lauca; growth rate; cushion plant; puna